Wine tourism activities as facilitators of relationship quality in wine sector - Cunha, N.; Loureiro, S. (Revista Turismo e Desenvolvimento/Journal of Tourism and Development, 2017)
This study aims to explore how wine producers and distributors and wine producers describe the organizational social capabilities they develop, as a facilitating facet of Relationship Quality (RQ). Therefore, we conducted and analysed 44 in-depth interview among members of top managers of wine producers and wine distributors. Findings highlight the organizational capabilities, social events and the players’ history as the core elements to develop an interactive relationship quality among stakeholders